Soybağının Tespiti Amacıyla İsteğe Dayalı Olarak Yapılan Gen İncelemeleri - SONAT, KAZIM ALİ (My University, 2013)
Gen incelemeleri, sağladığı ispat olanakları nedeniyle soybağı davaları kapsamında sıklıkla başvurulan bir bilimsel yöntemdir. Bu incelemenin, görülmekte olan bir davadan bağımsız olarak, salt isteğe dayalı olarak yapılması, soybağının tespiti bakımından dava yoluna başvurulmasına kıyasla ilgililere önemli avantajlar sağlamaktadır. Bu incelemeler, incelemeye katılanların ve üçüncü kişilerin kişilik değerlerine müdahale teşkil ettiğinden, kural olarak hukuka aykırıdır. Hukuka aykırılık, TMK m. 24/II uyarınca, kural olarak ilgililerin rızası ile önlenir. Rızanın geçerli olabilmesi ise aydınlatılmış bir irade temelinde, yetkili kişi tarafından ve şekle uygun olarak açıklanmış olmasına bağlıdır. Rızanın mevcut olmadığı durumlarda ise, çocuğun genetik kökenini öğrenme hakkı, üstün özel yarar teşkil ettiği ölçüde, gen incelemesinin hukuka aykırı olmasını önleyebilir

Genetic testing is a scientific method applied frequently within civil proceedings owing to probative value it provides. The fact that these tests are being done outside the context of proceedings by private demand provides significant advantages to persons concerned in comparison with the determination of filiation within civil proceeding. These tests are unlawfull as they cause intervention to personality rights of persons who take part directly in the tests and indirectly to third persons as well. On the bases of article 24/II of Turkish Civil Code, as a rule, the avoidance of illegality is possible with the consent of the persons concerned with test. Besides this, the validity of the consent depends on its being declared in compliance with the formal requirements, by authorized person who is informed properly. In the absence of consent, the child’s right to know his genetic origins can avoid genetic test from being unlawfull as long as this right is considered as an overriding private interest in the sense of article 24/II of Turkish Civil Code.
Keywords: Gen incelemesi; DNA analizi; isteğe dayalı gen incelemesi; soybağı; soybağının tespiti; kişilik hakkı; tıbbi müdahale; rıza; genetik kökenini öğrenme hakkı; üstün özel yarar; çocuğun menfaati; kayyımlık; Genetic test; DNA analysis; filiation; genetic analysis by private demand; determination of filiation; personality rights; medical act; consent; right to know his genetic origins; overriding private interest; deputyship